2020
DOI: 10.1007/s40194-020-00912-4
|View full text |Cite
|
Sign up to set email alerts
|

Residual stresses in thermite welded rails: significance of additional forging

Abstract: The aluminothermic welding (ATW) process is the most commonly used welding process for welding rails (track) in the field. The large amount of weld metal added in the ATW process may result in a wide uneven surface zone on the rail head, which may, in rare cases, lead to irregularities in wear and plastic deformation due to high dynamic wheel-rail forces as wheels pass. The present paper studies the introduction of additional forging to the ATW process, intended to reduce the width of the zone affected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Indeed, 'ALFONS' welding technology is an automated thermite welding process applying an additional forging load at the end of the process in a forging step. Josefson et al studied numerically this process [31]. The FE-simulations showed that the addition of forging load induces an increase in plastic strains within the welded area.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 'ALFONS' welding technology is an automated thermite welding process applying an additional forging load at the end of the process in a forging step. Josefson et al studied numerically this process [31]. The FE-simulations showed that the addition of forging load induces an increase in plastic strains within the welded area.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other energetic materials, thermite has the characteristics of high adiabatic temperature, high combustion efficiency, high enthalpy of reaction, good safety, flexible formula and so on, so it has an extensive application prospect. In the civil field, thermite is generally used in welding [5], thermal batteries [6] and metallurgy [7]. In the military area, thermite is widely used as an additive in ammunition destruction [8], infrared bait [9], solid rocket propellant and high-energy charge [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The thermite stands out due to its excellent combustion efficiency, high energy‐releasing rate, and high reaction exothermic enthalpy, which catches the attention of researchers. Thermite has been widely used in gas generator, 3 welding, 4 ammunition destruction 5 and high‐energy additives in propellants 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…The thermite stands out due to its excellent combustion efficiency, high energy-releasing rate, and high reaction exothermic enthalpy, which catches the attention of researchers. Thermite has been widely used in gas generator, 3 welding, 4 ammunition destruction 5 and high-energy additives in propellants. 6,7 The thermite composed of metal oxide and metal powder possesses unique chemical properties, which mainly is ascribed to the nature of its components.…”
Section: Introductionmentioning
confidence: 99%